(untitled) (Bulletin KNOB, 2008)
In 1932 the Utrecht architect Willem A. Maas (1897-1950) built the St Joseph teacher training college (5/ Jozef-Kweekschool) in Zeist for the friars of Utrecht. Against all expectations the complex did not get a traditional exterior: on the contrary, it was a concrete and iron frame construction, covered with clinkers, and because of the large window sections light and space were emphasized. Special attention was paid to the infirmary, in which Maas applied a variant of his system-Maas: a system of sliding walls and windows for optimal daylight access. Maas was to apply this system - devised for an open-air school - especially in hospital building, in which discipline he specialized after 1935. An important element of the St Joseph school was the chapel. Owing to its concrete construction and the abundance of light it signified an innovation in Roman-Catholic church building. As early as in 1925 Maas. co-founder and member of the editorial staff of the progressive Roman-Catholic journal De Gemeenschap, had considered the combination of constructivism and Catholicism in architecture and art. of which this chapel may serve as an example. In his own time Willem Maas still attracted a great deal of interest. After his death he passed into oblivion. He is practically absent from the surveys on Dutch architecture of the twentieth century. The St Joseph school marked an important moment in his oeuvre. It established Maas’s reputation as a modern and functional architect: the chapel was an important moment for the emancipation of Roman-Catholic church building. The more painful is the fact that particularly this chapel, as one of the first components of the complex, was demolished. In the present new construction, in which the architect claims to have incorporated the major characteristics of the building of Maas, only parts of the original construction have imperceptibly been included. The building is still a category 1 listed building on the municipal historic buildings register, a qualification that has become superfluous.